STRATEGI PEMASARAN DAN MANAJEMEN UMKM EFEKTIF DALAM MENINGKATKAN DAYA SAING DI ERA PASAR ONLINE PADA PELATIHAN KECAKAPAN WIRAUSAHA DI LKP KAWAICI NN KABUPATEN DEMAK - Widodo, Untung; Indriyatni, Lies; Wahyunigsih, Susanti; Yuliati, Yuliati (Fokus ABDIMAS, 2025)
This community service activity aims to improve the skills and understanding of entrepreneurship training participants at LKP Kawaici NN, Demak Regency, in implementing effective marketing strategies in the digital era. The methods used include training sessions, mentoring, and hands-on practice in utilizing social media and online marketplaces as marketing platforms. The results of the activity show an increase in participants’ understanding of digital marketing concepts, their ability to create promotional content, and their confidence in selling products online. Therefore, this training has had a positive impact on enhancing the participants’ competitiveness in the online market.